Segmentacja regionalna i konkurencyjność jako podstawy lokalizacji przestrzennej przedsiębiorstwa zagranicznego - Sobczak, Elżbieta (Regional segmentation and competitiveness as the basis for spatial localisation of a foreign enterprise, 2006)
The objective of the hereby study is to suggest regional segmentation based on regions’ competitiveness assessment, as the means for selecting spatial localisation of a foreign enterprise activities. The basis for such segmentation becomes evaluation of the interregional diversification significance as well as the means-end chains (MEC) concept. The key idea underlying MEC is that competitive attributes of a region are the means for an enterprise, which facilitate obtaining the desirable objectives, namely direct advantages and values. Configurations of attributes, advantages and values relations result in countries and regions diversifications, therefore they may become the basis for their classification.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 238-247